2007
DOI: 10.1016/j.exphem.2007.01.049
|View full text |Cite
|
Sign up to set email alerts
|

RTP801 is a novel retinoic acid–responsive gene associated with myeloid differentiation

Abstract: Objective-Retinoids are crucial in the regulation of fundamental cellular processes including terminal differentiation of both normal and malignant myeloid progenitors. The aim of this study was to identify and characterize retinoic acid (RA) target genes.Methods and Results-RTP801 is a recently cloned stress response gene that acts as a negative regulator of the mTOR pathway. Here we identified RTP801, as a novel early RA target gene in myeloid cells. RTP801 mRNA levels are induced in acute myeloid leukemia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…42 It has further been shown that this effect of ATRA is mediated through the stress response gene RTP801, an early RA target gene in myeloid cells, which acts as a negative regulator of the mTOR pathway. 42,43 Further, autophagic death of acute lymphoblastic lymphoma cells treated with dexamethasone was recently shown to be dependent on the PML protein, which is known to represent an inhibitor of mTOR activity. 44,45 Thus, mTOR-regulated autophagy may play a general role in development and treatment of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…42 It has further been shown that this effect of ATRA is mediated through the stress response gene RTP801, an early RA target gene in myeloid cells, which acts as a negative regulator of the mTOR pathway. 42,43 Further, autophagic death of acute lymphoblastic lymphoma cells treated with dexamethasone was recently shown to be dependent on the PML protein, which is known to represent an inhibitor of mTOR activity. 44,45 Thus, mTOR-regulated autophagy may play a general role in development and treatment of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…RTP801 is a negative regulator of the mTOR pathway. 37 It is unlikely that MS-275 induced differentiation of AML cells and inhibited mTOR signaling through RTP801. MS-275 inhibited both Akt and mTOR ( Figure 1); however, RTP801 was shown to inhibit mTOR but not Akt.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the cellular compartment in which REDD1 resides for mTORC1 regulation is likely to be a tritoninsoluble membrane fraction which contains the majority of cellular Rheb, the target of REDD1-TSC1/2 activity (16). Although the specific mechanism of REDD1 function in the mitochondria awaits further studies, REDD1 has been reported to interact with mitochondrial proteins in vitro (26), suggesting the possibility of a direct effect of REDD1 on electron transport.…”
Section: Consequently Redd1mentioning
confidence: 99%